Self-criticism or “Potestas”? (Journal of Parents and Teachers, 2013)
It treats  of a reflection, from the own experience and the one of  the Galicia Seminar of Education for Peace,  on the open debate in relation with the designated “Authority” Of the teachers in the school and in the current society, on the changes that have produced  in the education in general, and in the family, in the last years in Spain, on the context in which it arises the debate on the authority of  the educational, to the light of the classical differentiation between the concept “self-criticism” and the concept “Potestas”.
Keywords: Authority; Education; opinion